Behaviour of woven hybrid basalt-carbon/epoxy composites subjected to laser shock wave testing: Preliminary results. (1st September 2015) - Ferrante, L.; Tirillò, J.; Sarasini, F.; Touchard, F.; Ecault, R.; Vidal Urriza, M.A.; Chocinski-Arnault, L.; Mellier, D.
Abstract: This study addresses the effect of basalt fibre hybridization on the damage tolerance of carbon/epoxy laminates subjected to laser shock wave tests. Interply hybrid specimens with two different stacking sequences (sandwich-like and intercalated) were tested at different laser intensities and residual post-shock properties of the different configurations have been characterized by quasi-static three point bending tests monitored by acoustic emission. Results indicate that the best compromise in terms of both quasi-static properties (2% reduction in flexural strength compared to all carbon laminates) and damage tolerance appears to be the sandwich-like structure with basalt fibre skins. In particular, this configuration exhibited the highest damage tolerance among the hybrids, with a percent decrease in flexural strength of about 5% compared to 15% in the case of all carbon laminates. Damage induced by laser shock testing in carbon-basalt woven fabric/epoxy composites is mainly inter-ply delamination. This study also highlights the tougher behaviour of basalt plies in response to a sudden application of load compared to carbon layers with a favourable hybridization effect.